The Translation Methods Applied By Two Indonesian Translators In Translating â€œThe Masque Of The Red Deathâ€ - Astiari, Komang (Denpasar Institute, 2021)
This research analyzed the methods applied in translating English short story â€œThe Masque of the Red Deathâ€ into Indonesian by two Indonesian translators; Anton Kurnia and Shinta Dewi. In the action of pointing out the methods, the theory of translation method proposed by Newmark was the foundation of the study. The translation methods emphasize the source language and target language. Since translation is both a means of a process and a product, this study also analyzed the readability level of the two translation results. In order to assess the readability, this research involved 7 respondents. Every respondent filled in the questionnaire given related to the product of the short story with open-ended questions. Readability was measured using the theory of Readability stated by Nababan. The outcome gained from this research was different translation methods applied by the two Indonesian translators had affected the readability level as well as the sense of the short story by the target readers. According to the findings, the translation methods used by Anton Kurnia was dominated by free translation method. In contrast to Anton Kurnia, Shinta Dewi frequently adopted literal translation method. Although the distinction of readability level was not very significant between the two, the method which emphasized the target language culture indicated a higher level of readability than the method which emphasized the source language culture.Culture